Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.0305180911091202.a01
|View full text |Cite
|
Sign up to set email alerts
|

Cerium and Cerium Compounds

Abstract: Cerium is the most abundant member of the lanthanide series, those elements having 4 f electrons. It is found in nature in the presence of other lanthanides and this mix is often used commercially as a cerium source without separation. Mischmetal, a metallic mix of cerium and other of the lighter lanthanides, is used in the steel industry, in lighter flints, and as getters. Lanthanide concentrate, an oxide mix that includes cerium oxide, is used in some fluid cracking catalysts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The cerium is the most important element of Lanthanide series and 26 th most abundant rare earth element forming 66 parts per million in the earth's crust ( Hu et al, 2006) with unique magnetic, electronic and catalytic properties (Hu et al, 2006;Bouzigues et al, 2011). It is ductile, malleable, irongray (O'Niel, 2001) and very strong oxidizing agent (Kilbourn, 2003). Cerium oxide is the most important compound in the form of heavy powder having paleyellow or brown color high melting point 2400 °C and density 7.65 g/cm 3 .…”
Section: Why Nano-cerium Important To Investigatementioning
confidence: 99%
See 2 more Smart Citations
“…The cerium is the most important element of Lanthanide series and 26 th most abundant rare earth element forming 66 parts per million in the earth's crust ( Hu et al, 2006) with unique magnetic, electronic and catalytic properties (Hu et al, 2006;Bouzigues et al, 2011). It is ductile, malleable, irongray (O'Niel, 2001) and very strong oxidizing agent (Kilbourn, 2003). Cerium oxide is the most important compound in the form of heavy powder having paleyellow or brown color high melting point 2400 °C and density 7.65 g/cm 3 .…”
Section: Why Nano-cerium Important To Investigatementioning
confidence: 99%
“…Chemically it is prepared by the reaction of CF3 with excess supply of calcium at 900 °C (O'Niel, 2001). It can also be prepared by cerium chloride and fluoride during the fused-salt electrolysis (Kilbourn, 2003). Nano-cerium is produced through aqueous precipitation (Sreeremya et al, 2012), sol-gel, thermal decomposition (Lin et al, 2010), hydrothermal (Yu et al, 2004), solvothermal oxidation flame spray (Madler et al, 2002), reversed micelles, aqueous precipitation and microwave assisted solvothermal process (Sreeremya et al, 2012).…”
Section: Why Nano-cerium Important To Investigatementioning
confidence: 99%
See 1 more Smart Citation
“…Cerium is unique among the REE in that both of its oxidation states are readily accessible in aqueous solution. Several specialized applications of Ce, notably polishing of glass, exploit this property (Kilbourn, 1992(Kilbourn, , 1993b.…”
Section: The Rare Earth Elementsmentioning
confidence: 99%
“…Recent studies performed using this exposure system have shown that altered cellular responses can be associated with the intracellular accumulation of CeO 2 NPs in lung cells in vitro over time (28,47). CeO 2 was specifically chosen as it is a representative industrial particle, due to its wide use as pigment and polishing agents, as well as a fuel catalyst (48,49). Additionally, recent studies have reported that cerium-containing particles were found in the lungs of workers who were exposed to CeO 2 aerosols at their workplaces (50,51,52,53,54).…”
Section: An Exposure System To Study the Effects Of Occupational Expomentioning
confidence: 99%